Potential role of compost mixed biochar with rhizobacteria in mitigating lead toxicity in spinach - Zafar-Ul-Hye, Muhammad; Tahzeeb-Ul-Hassan, Muhammad; Abid, Muhammad; Fahad, Shah; Brtnicky, Martin; Dokulilova, Tereza; Datta, Rahul; Danish, Subhan (Scientific reports, 2020)
Consumption of heavy metals, especially lead (Pb) contaminated food is a serious threat to human health. Higher Pb uptake by the plant affects the quality, growth and yield of crops. However, inoculation of plant growth-promoting rhizobacteria (PGPR) along with a mixture of organic amendments and biochar could be an effective way to overcome the problem of Pb toxicity. That's why current pot experiment was conducted to investigate the effect of compost mixed biochar (CB) and ACC deaminase producing PGPR on growth and yield of spinach plants under artificially induced Pb toxicity. Six different treatments i.e., control, Alcaligenes faecalis (PGPR1), Bacillus amyloliquefaciens (PGPR2), compost + biochar (CB), PGPR1 + CB and PGPR2 + CB were applied under 250 mg Pb kg-1 soil. Results showed that inoculation of PGPRs (Alcaligenes faecalis and Bacillus amyloliquefaciens) alone and along with CB significantly enhanced root fresh (47%) and dry weight (31%), potassium concentration (11%) in the spinach plant. Whereas, CB + Bacillus amyloliquefaciens significantly decreased (43%) the concentration of Pb in the spinach root over control. In conclusion, CB + Bacillus amyloliquefaciens has the potential to mitigate the Pb induced toxicity in the spinach. The obtained result can be further used in the planning and execution of rhizobacteria and compost mixed biochar-based soil amendment.
Keywords: symbióza; olovo; Bacillus amyloliquefaciens; Potassium; Lead; Carbon-Carbon Lyases; draslík; Bacterial Proteins; Plant Roots; Chlorophyll; Hydrogen-Ion Concentration; látky znečišťující půdu; Soil Microbiology; Spinacia oleracea; Soil; Soil Pollutants; kořeny rostlin; koncentrace vodíkových iontů; chlorofyl; Charcoal; bakteriální proteiny; půdní mikrobiologie; Symbiosis; lyasy štěpící vazby C-C; Alcaligenes faecalis; půda; dřevěné a živočišné uhlí